#TITLE_ALTERNATIVE# - SEPTAVYN (NIM : 13205124); Pembimbing : Dr. Ir. Muhammad Nurdin ; Dr.Ir.Nanang Haryanto, MT., ROBIN
Distributed Generation is the concept of generating electrical energi using generators scattered - small plants around the load center. The use of DG as an emergency supply initially, gradually become a popular concept in some countries, given the need for environmentally friendly power plants and the depletion of reserves of fossil energi sources. Interconnection of DG to the distribution system needs to consider several things, one of which is the location of DG placement and capacity can be generated. Both these factors are critical to the impact of DG interconnection on system performance, especially in terms of losses of power and voltage quality in each bus. That allocation becomes a problem that must find the optimal solution. This final project discusses an optimization method in terms of determining the location and capacity of Distributed Generation (DG) using a Genetic Algorithm (GA). GA is used as a means of solving problems of optimization with the problems that have been previously defined and the objective function has been determined. Objective function in the form of losses of system power obtained from power flow analysis. Power flow analysis combined with GA, to achieve the most optimal solution. This method was tested on 28 bus distribution system with a total installed DG is five DG.